The honor dress of the movement : a cultural history of Hitler's brown shirt uniform, 1920-1933 - Homberger, Torsten, 1976- (University of Massachusetts Press, 2021)
"During the era of the Weimar Republic, Germany was characterized by deep contradictions and polarizations. New, progressive social mores and artistic developments mixed uneasily with growing reactionary politics. When the 1929 stock market crash produced a severe economic shock, voters began to shift their allegiances from the parties of the center to radicals on both the left and the right. By 1933, amidst crisis and chaos, the Nazis had taken over. In The Honor Dress of the Movement, Torsten Homberger contends that the brown-shirted Stormtrooper uniform was central to Hitler's rise to power. By analyzing its design and marketing, he investigates how Nazi leaders used it to project a distinct political and military persona that was simultaneously violent and orderly, retrograde and modern-a dual image that proved popular with the German people and was key to the Nazis' political success. Based on a wealth of sources that includes literature, films, and newspapers of the era, Homberger exhibits how the Nazis shaped and used material culture to destroy democracy"--